Assessing SMEs tax non-compliance behaviour in Sub-Saharan Africa (SSA): An insight from Nigeria - Olusegun Vincent (Taylor & Francis Group, 2021)
The existing studies on determinants of small and medium enterprises (SMEs) tax compliance behaviour in Sub-Saharan Africa have been criticised on account of limited study scope which compromises generalisation and poor theorisation that have little or no support for the research questions of such studies. The current study is rooted in behavioural economics theory and elicits information from 392 participants from all geopolitical zones of Nigeria using paper-and-pencil survey instruments. The study’s findings reveal that tax system complexity, tax deterrence sanction, tax non-compliance opportunity, tax information and tax attitude and perception are important determinants of tax compliance behaviour, while tax rate and tax compliance cost may not necessarily exert significant influence. The overall conclusion from the study reveals that certain economic and behavioural factors are effective in either encouraging or discouraging tax compliance behaviour. The study also reveals tax information to be one of the most significant drivers of tax compliance; however, little or nothing is known of this construct in the existing literature. The theoretical and policy implications of the study are discussed and suggestions for future studies are offered.